RESPLIESTA PRODUCTIVA DE LAS CERDAS A TRES FUENTES DE ENERGIA EN LA DIETA DE LACTACION - Jorge Oliva Hernández; Felipe Rosas Morales; Alejandro Villa Godoy; José A. Cuarón Ibargüengoytia (Revista Mexicana de Ciencias Pecuarias, 2012)
-